Effect of Rhizobium culture in combination with organic and chemical fertilizers on rajmash (Phaseolus vulgaris) under dry temperate conditions of Himachal Pradesh - RANA, M C; DATT, N; SINGH, MAN (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during the rainy (kharif’) seasons of 2000 to 2003 at the research farm of Highland Agricultural Research and Extension centre, Kukumseri, Lahaul and Spiti to study the efTect of Rhizobium culture in combination with organic and chemical fertilizers on yield of rajmash (Phaseolus vulgaris L.). Twelve treatments comprising of combination of seed treatment (with and without Rhizobiulll), farmyard manure (0, 5 and 10 tonnes/ha) were tested at 2 levels of fertilizer application (50 and 100 %) of recomn1ended (40:60:30) in factorial randomized block design. The results revealed that application of 10 tonnes farmyard manure Iha resulted better than 5 tonnes farmyard manure /ha with respect to all the yield contributing characters, yield parameters and N,P,K uptake, whereas the trend in efficiency ratio of N,P,K and physiological efficiency index ofabsorbed N,P,K were found just reverse to the trends found in N,P,K uptake. undred per cent of fertility level also influenced the plant height, pods/plant, grains/pod, nodule fresh weight / plant, seed and straw yields and N,P,K uptake significantly than 50% of fertility leve1.The efficiency ratio ofN,P,K and physiological efficiency index of absorbed N,P,K were found higher with low fertility level ,i e 50% of recommended than 100% of reco111n1ended level. Significantly more plant height, pods / plant, grains / pod, module count and their fresh weight per plant, seed and straw yield, N,P and K uptake recorded in seed inoculation with Rhizobiunz culture than no seed inoculation, whereas the efficiency ratio of N,P,K and physiological efficiency index of absorbed N,P,K were recorded higher with no Rhizobiunz inoculation treatment than Rhizobium inoculation.